Funkcja tworzaca Horqu: Znajdz funkcje tworzaca ciagu rekurencyjnego zadanego zaleznoscia: an=−6*an−1−9*an−2+16n+8 dla n>=2 a0=3 a1=9
12 sty 20:36
Pytający: A(x) = = ∑n=0(anxn) = = a0x0 + a1x1 + ∑n=2(anxn) = = 3 + 9x + ∑n=2((−6an−1 − 9an−2 + 16n + 8)xn) = = 3 + 9x −6n=2(an−1xn) −9n=2(an−2xn) +8n=2((2n+1)xn)=
 x2(5 − 3x) 
= 3 + 9x − 6(x*A(x) − 3x) − 9(x2*A(x)) + 8(

) =
 (1 − x)2 
 8x2(5 − 3x) 
= 3 + 9x − 6x*A(x) + 18x − 9x2*A(x) +

=
 (1 − x)2 
 8x2(5 − 3x) 
= 3 + 27x − 6x*A(x) − 9x2*A(x) +

 (1 − x)2 
 8x2(5 − 3x) 
A(x) + 6x*A(x) + 9x2*A(x) = 3 + 27x +

 (1 − x)2 
 8x2(5 − 3x) 
(1 + 6x + 9x2)*A(x) = 3 + 27x +

 (1 − x)2 
 
 8x2(5 − 3x) 
3 + 27x +

 (1 − x)2 
 
A(x) =

= ← WYNIK
 (1 + 6x + 9x2) 
 
 8x2(5 − 3x) 
3 + 27x +

 (1 − x)2 
 
=

=
 (3x + 1)2 
 3x3 − 11x2 + 21x + 3 
=

 (x − 1)2 (3x + 1)2 
n=2(an−1xn) = = ∑n=1(anxn + 1) = = x∑n=1(anxn) = = x(∑n=0(anxn) − a0x0) = = x(A(x) − 3) = = x*A(x) − 3x • n=2(an−2xn) = = ∑n=0(anxn+2) = = x2*∑n=0(anxn) = = x2*A(x) • n=2((2n + 1)xn) = = ∑n=0((2(n + 2) + 1)xn+2) = = x2n=0((2(n + 2) + 1)xn) = = x2n=0((2(n + 1) + 3)xn) = = x2(2∑n=0((n + 1)xn) + 3∑n=0(xn)) =
 1 1 
= x2(2*

+ 3*

) =
 (1 − x)2 1 − x 
 2 + 3(1 − x) 
= x2*

=
 (1 − x)2 
 x2(5−3x) 
=

 (1 − x)2 
13 sty 14:53